2021
DOI: 10.1002/biof.1732
|View full text |Cite
|
Sign up to set email alerts
|

The unique molecular targets associated antioxidant and antifibrotic activity of curcumin in in vitro model of acute lung injury: A proteomic approach

Abstract: Bleomycin (BLM) injury is associated with the severity of acute lung injury (ALI) leading to fibrosis, a high‐morbidity, and high‐mortality respiratory disease of unknown etiology. BLM‐induced ALI is marked by the activation of a potent fibrogenic cytokine transcription growth factor beta‐1 (TGFβ‐1), which is considered a critical cytokine in the progression of alveolar injury. Previously, our work demonstrated that a diet‐derived compound curcumin (diferuloylmethane), represents its antioxidative and antifibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…For example, it has been reported that in hepatocellular carcinoma, the expression levels of CDK1 was positively correlated with the infiltration levels of CD4 + T cells, CD8 + T cells, neutrophils, macrophages and dendritic cells, suggesting that this gene may be involved in the recruitment and regulation of infiltrating cells in the immune microenvironment [ 33 ]. And in Bleomycin-induced ALI, the protein expression of Top2a was up-regulated, which leads to persistent inflammation and aggravation of alveolar epithelium [ 34 ]. Thus, these genes may be involved in immune regulation and inflammation balance in PBLI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that in hepatocellular carcinoma, the expression levels of CDK1 was positively correlated with the infiltration levels of CD4 + T cells, CD8 + T cells, neutrophils, macrophages and dendritic cells, suggesting that this gene may be involved in the recruitment and regulation of infiltrating cells in the immune microenvironment [ 33 ]. And in Bleomycin-induced ALI, the protein expression of Top2a was up-regulated, which leads to persistent inflammation and aggravation of alveolar epithelium [ 34 ]. Thus, these genes may be involved in immune regulation and inflammation balance in PBLI.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 protein levels were evaluated using Human TGF-β1 ELISA Kit (KRISHGEN biosystems, Mumbai, India). In addition, fibronectin and hydroxyproline were estimated by spectrophotometric and immunoassay techniques, as previously reported [116][117][118]. The absorbance (OD) of hydroxyproline in the supernatant of cancer cell lines was determined at wavelength 557 nm using a Systronics-2203 spectrophotometer (Systronics, Gujarat, India) [117].…”
Section: Assessment Of Cellular Fibrosismentioning
confidence: 99%